REPORTING ENTITIES IN COMMERCIAL LAW - Мілімко, Лариса Василівна; Крейцман, Дмитро Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to characterize the legal regulation of the financial monitoring and the reporting entities as individual participants in commercial relations; to identify problems and make suggestions for improving the legal regulation of their activities. Methods: the study was conducted using methods such as analysis, synthesis, comparison. Results: the characteristic is given to the legal regulation of the financial monitoring; business entities, that are responsible for performing primary financial monitoring, are identified; the proposals are formulated to the Law of Ukraine «On prevention and counteraction to proceeds from crime legalization (laundering), to financing of terrorism and to financing of mass destruction weapons proliferation». The problem of corruption among the participants of economic relations and the government officials at all the levels has existed since Ukraine’s independence and this problem remains still relevant. It hinders the successful development of the country’s economy, it’s individual industries, and society as a whole; it does not allow the proper use of the existing resource and human potentials to improve the living standards and well-being of population majority of Ukraine. An appropriate regulatory framework has been created in Ukraine for the purpose of prevention and counteraction to proceeds from crime legalization (laundering), to financing of terrorism and to financing of mass destruction weapons proliferation. This regulatory framework has been changing and evolving for over 18 years. Certainly, the relevant measures have brought the national legal framework for the prevention of money laundering closer to EU standards, and have created a state system for financial transactions monitoring that could potentially be associated with the dangerous crimes. The peculiarity of this system is that the supervisory and security functions in accordance with current legislation are entrusted not only to public law enforcement agencies, fiscal service or other control institutions with some special status, but also to ordinary participants in economic relations: legal entities (primarily banks) ), individual entrepreneurs, individuals engaged in independent professional activities (private notaries, lawyers, auditors, accountants), whose competence includes the implementation of economic and legal transactions with property that may have signs of criminal origin. Entities endowed with these powers are the reporting entities. However, despite the existence of an appropriate monitoring system, in fact, the Ukraine’s capital outflow to other economic territories has not significantly decreased, also proceeds from crime are freely and unhinderedly invested in real estate. This indicates an efficiency lack of the existing financial monitoring system. This article is devoted to the problem of the financial monitoring system efficiency, and to insufficient level of reporting entities involvement.